Increased placental expressions of nuclear factor erythroid 2–related factor 2 and antioxidant enzymes in gestational diabetes: Protective mechanisms against the placental oxidative stress?. (July 2019) - Manoharan, Balachandiran; Bobby, Zachariah; Dorairajan, Gowri; Jacob, Sajini Elizabeth; Gladwin, Victorraj; Vinayagam, Vickneshwaran; Packirisamy, Rajaa Muthu
Abstract: Objective: Gestational diabetes mellitus is associated with increased oxidative stress. Oxidative stress may contribute to the risk for pregnancy pathologies associated with gestational diabetes mellitus. In this study we investigated the expression of placental nuclear factor erythroid 2–related factor 2 (Nrf2) and antioxidant enzymes of gestational diabetes mellitus and healthy pregnant women and correlated them with the maternal and cord plasma as well as placental tissue oxidative stress parameters. Study design: A cross sectional study was carried out in a South Indian Tamil population. Forty healthy pregnant women and forty gestational diabetes mellitus patients in the gestational age of 32 ± 4weeks were recruited. Maternal plasma, cord plasma and placental oxidative stress parameters were measured. Placental expression of Nrf2, phospho Nrf2, catalase and superoxide dismutase 1(SOD1) were analyzed by western blotting and immunohistochemistry. Results: Placental expression of Nrf2, catalase and SOD1 were found to be significantly higher in gestational diabetes mellitus. The maternal plasma, cord plasma and placental tissue oxidative stress parameters, total antioxidant status (TAS) levels were significantly lower; whereas MDA (malondialdehyde) and MDA/TAS levels were significantly higher in gestational diabetes mellitus. Placental Nrf2 expression correlated positively with the placental catalase expression and negatively with placental TAS levels in both groups. Conclusion: Maternal, fetal and placental oxidative stress was observed in gestational diabetes mellitus. The gestational diabetic placenta had an increased Nrf2 protein expression. The activated placental Nrf2/ antioxidant response element (ARE) pathway might have led to an increased expression of antioxidant enzymes SOD1 and catalase. This may be viewed as a protective mechanism in placenta from the further onslaught of oxidative stress.